Author Correction: Expression-based drug screening of neural progenitor cells from individuals with schizophrenia. Issue 1 (December 2018) - Readhead, Benjamin; Hartley, Brigham; Eastwood, Brian; Collier, David; Evans, David; Farias, Richard; He, Ching; Hoffman, Gabriel; Sklar, Pamela; Dudley, Joel; Schadt, Eric; Savić, Radoslav; et al.
In the originally published version of this Article, the affiliation details for Eric E. Schadt and Radoslav Savic incorrectly omitted 'Sema4, a Mount Sinai venture, Stamford, Connecticut, USA'. This has been corrected in both the PDF and HTML versions of the Article.